Progress and Challenges in the Field of Snakebite Envenoming Therapeutics - Gutiérrez, José María (2024)
Snakebite envenoming kills and maims hundreds of thousands of people every year, especially in the rural settings of tropical regions. Envenomings are still treated with animal-derived antivenoms, which have prevented many lives from being lost but which are also medicines in need of innovation. Strides are being made to improve envenoming therapies, with promising efforts made toward optimizing manufacturing and quality aspects of existing antivenoms, accelerating research and development of recombinant antivenoms based on monoclonal antibodies, and repurposing of small-molecule inhibitors that block key toxins. Here, we review the most recent advances in these fields and discuss therapeutic opportunities and limitations for different snakebite treatment modalities. Finally, we discuss challenges related to preclinical and clinical evaluation, regulatory pathways, large-scale manufacture, and distribution and access that need to be addressed to fulfill the goals of the World Health Organization's global strategy to prevent and control snakebite envenoming.